Subjective perceptions of father’s educational attitudes among adolescent girls with different degrees of codependency - Stepanova, Ludmila G.; Savitskaya, Anastasiya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article deals with the actual problem of peculiarities of relationships with the father in girls with different degrees of codependency. The article also presents the results of the empirical study of the peculiarities of subjective perc eptions of father’s educational attitudes in adolescent girls with different degrees of codependency. It was found that the de gree of codependency is higher in girls who evaluate their father’s educational attitudes as destructive, characterised by hostility and inconsistency. The conclusions drawn are of decisive importance for the development of basic strategies for psychological support of the educational activities of adolescents suffering from codependency, in order to prevent and timely correct destructive states and increase the level of personal autonomy, as well as psychological and pedagogical support of the educational activities of fathers so that they acquire the necessary competencies.
Keywords: codependency; codependent behaviour; father’s educational attitudes; perceptions of the father; family; adolescent girls